Laser powder bed fusion of invar-based metal matrix composites reinforced with ceramic particles: relationships between residual stresses, microstructure, and mechanical properties - Oyedeji, Ayodeji Nathaniel (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2025.